Analisis Perhitungan Efektivitas Mesin Mobile Crusher Menggunakan Metode Overall Equipment Effectiveness (OEE) Di PT. X - Anggraini, Meilani; Sidiq, Ahmad; Hartiwi, Intan (Fakultas Teknik Universitas Tulang Bawang, 2025)
PT. X is a manufacturing company that produces cram rubber. One of the production processes that need attention is the milling process on mobile crusher machines. Machine is the highest support in the activities of a company, if the machine used in the production process is damaged it will cause a cessation of the production process. To maintain the condition of the machine, a good and appropriate care and maintenance system is needed so as to increase the effectiveness of the machine/equipment. The aim of this study is to analyze OEE calculations and identify factors that occur in mobile crusher machines based on the Six Big Losses at PT. X. OEE is a method that measures the level of effectiveness in the use of a machine by taking into account several points of view in the measurement process. The results of the study, it show the average of OEE value for mobile crusher machine during the June 2021 – July 2022 is 82,021% which shows that the machine’s ability to achieve targets and achieve effective use of machines is in the medium category, so improvements are needed to increase the OEE value to reach ideal conditions (≥85%). Meanwhile, the dominant type of waste is reduced speed losses. Keywords: Mobile Crusher Machine, Overall Equipment Effectiveness, Six Big Losses